An Assessment of the Role of Women Group in Women Political Participation, and Economic Development in Nigeria - Orisadare, Monica Adele (Frontiers in Sociology, 2019)
The exclusion of women in politics has been identified in recent times as one of the major setbacks for economic development. Women's groups are a strong pillar for grassroots politics; and a drive for more women participating in politics at the grassroots still faces a lot of challenges, making it difficult for them to harness available opportunities for economic development. Thus, the opportunity therein for more women's participation in politics and women empowerment is yet to be exploited by the women's groups in Nigeria. This present study assesses the role of women's groups in politics, identifies their challenges and also explores its implication for economic development in Osun state, Nigeria. The study was carried out using primary data from forums and dialogues within women's groups, consisting of an average of thirty (30) members from ten (10) local government areas (LGAs) in Osun state, Nigeria. In addition, explorative methods using existing literature were also employed. Findings from the study indicate that women's groups do not have political agenda; mostly, their goals do not align with any political agenda, although their members accept appointments, and also enjoy government patronage. There was also an indication that there exists a high illiteracy rate among the members of the women's groups and most of them are not aware of existing National or International gender equality laws or affirmative action. Thus, it is difficult to participate in politics and contribute their voices to political issues. The study concludes that the present role played by women's groups at the grassroots level may not be adequate in encouraging more women's participation in politics and in influencing economic development. Thus, there is need to step up their activities and embrace political issues if they are to help more women participate and be relevant in politics. The study therefore suggests that more empowerment programs, especially in the area of decision making and participation in politics, should be targeted at women's groups at the grassroots levels by the governments and all stakeholders as a matter of priority.